2003
DOI: 10.1074/jbc.m212776200
|View full text |Cite
|
Sign up to set email alerts
|

RhoA Expression Is Controlled by Nitric Oxide through cGMP-dependent Protein Kinase Activation

Abstract: Small G proteins of the Rho family function as tightly regulated molecular switches that govern a wide range of cell functions (1). A large body of evidence has now been obtained regarding the important functions of Rho proteins in the vasculature, and RhoA has been shown to play a major role in vascular processes such as smooth muscle cell contraction, proliferation, and differentiation; endothelial permeability; platelet activation; and leukocyte migration (2-4). The activity of Rho is under the direct contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 41 publications
8
128
0
2
Order By: Relevance
“…The involvement of other proteins may explain this effect because cGMP/cGK signaling may control cell shape in different cell models by regulating either the expression or activity of the RhoA GTPase. 38,39 It is believed that RhoA suppresses neurite outgrowth 31 and thus, an increase in RhoA activity in sGCb1depleted cells might also explain the inhibition of neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of other proteins may explain this effect because cGMP/cGK signaling may control cell shape in different cell models by regulating either the expression or activity of the RhoA GTPase. 38,39 It is believed that RhoA suppresses neurite outgrowth 31 and thus, an increase in RhoA activity in sGCb1depleted cells might also explain the inhibition of neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that RhoA was rapidly activated and then upregulated at the transcriptional level in response to HLA class I ligation on vascular EC. To our knowledge and as reported in recent publications (23,24), regulation of RhoA at a transcription or protein level is almost unknown. These studies showed an increase of RhoA mRNA associated with enhanced RhoA protein level.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that lipid-lowering effects of Rho-kinase inhibition are mediated by AMPK phosphorylation but not by eNOS activation. Rho-kinase causes instability of eNOS mRNA (Takemoto et al 2002), whereas NO inhibits RhoA expression and Rho-kinase activity (Sauzeau et al 2003;Kato et al 2012). Moreover, Rho-kinase inhibits phosphorylation of Akt (Wolfrum et al 2004) and AMPK (Noda et al 2014), the up-stream molecules of eNOS.…”
Section: Negative Interactions Between No and Rho-kinase In Lipid Metmentioning
confidence: 99%
“…Since Rho-kinase inhibited the expression and activity of eNOS (Takemoto et al 2002;Sauzeau et al 2003), we examined the effects of fasudil on eNOS expression and activity in WT mice. As expected, long-term treatment with fasudil significantly enhanced eNOS phosphorylation, expression and activity (as evaluated by phosphorylated/ total eNOS) in the liver of HFD-fed WT mice (Fig.…”
Section: Fasudil Increases Enos Expression and Phosphorylation In Hfdmentioning
confidence: 99%
See 1 more Smart Citation